The unity of rational and emotional aspects of educational activities of future specialists in the art of music (Pedagogy of Higher and Secondary Education, 2011)
The problem of rational and emotional means of art mastering unity is actualized; essence of consolidation unity of cognitive-searching, estimation-interpretative and creative-productive kinds of educational activity of music-pedagogical profile specialists is educated.
Keywords: music art specialists; cognitive-searching; estimation-interpretative; creative-productive activity